If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2(y + -5) = 0 Reorder the terms: 3x + -2(-5 + y) = 0 3x + (-5 * -2 + y * -2) = 0 3x + (10 + -2y) = 0 Reorder the terms: 10 + 3x + -2y = 0 Solving 10 + 3x + -2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + 3x + -10 + -2y = 0 + -10 Reorder the terms: 10 + -10 + 3x + -2y = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 3x + -2y = 0 + -10 3x + -2y = 0 + -10 Combine like terms: 0 + -10 = -10 3x + -2y = -10 Add '2y' to each side of the equation. 3x + -2y + 2y = -10 + 2y Combine like terms: -2y + 2y = 0 3x + 0 = -10 + 2y 3x = -10 + 2y Divide each side by '3'. x = -3.333333333 + 0.6666666667y Simplifying x = -3.333333333 + 0.6666666667y
| 3x^4-3x^2+1=0 | | 2(W+4)-3(W+4)=0 | | 6-z=-8 | | X^4-4*x^3+8x= | | y=x^2+1.5xfor-2 | | 2(0)+7y=28 | | y-14=-11 | | 21x+3=17x+15 | | 3t-2=5t+4 | | (7b-1)-2(3b+3)=-2 | | 50x+13=12 | | 3(x^2-5(x+2(3-5x)))= | | 7-z=5 | | 10-6z=-62 | | 21x+3+17x+15=180 | | X^2n-5=11 | | 3-z=-10 | | 10-d=37 | | 12x+1+3*(x+5)=1 | | 90+.5x=50+.9x | | 3cos(6x)sin(5y)=4 | | 4(g+7)=68 | | 2x^2+4x-117=0 | | -4x+5x-8+4=-3x+5-9 | | W-5=-(5-w) | | 64x^2-kx=1 | | 8x^3=64 | | 18x-x+30=0 | | 13d+560m=595 | | 4(2x+7)=-2(x+6)-1 | | 16d+760m=754 | | 1+0.8x+0.6x^2=0 |